PERFORMANCE OF VILLAGE APPARATUS: CASE STUDY LEMPE VILLAGE OFFICE IN DAMPAL SELATAN DISTRICT, TOLI-TOLI DISTRICT - Mustainah, Mustainah (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
The aim of this research is to find out how the Village Officials perform at the Lempe Village Office, South Dampal District, Toli-Toli Regency. The method in this research is descriptive qualitative. The types of data used in this research are primary data and secondary data. The data collection technique in this research is by observation, interviews accompanied by direct documentation. There were 5 informants in this research, namely, the Village Head, Village Secretary, and 3 village residents. According to Suyadi Prawirosentono, the theory used in this research consists of 4 indicators, namely, Effectiveness, Responsibility, Discipline and Initiative. Based on the research results obtained, it can be concluded that the performance of village officials at the Lempe Village Office, South Dampal District, Toli-Toli Regency is quite good. It's just that there are still some things that are still not optimal, such as there are still officers who lack discipline in terms of time discipline. Many officers are late for work and some are found not to be at work during working hours. Lempe Village officials still show a lack of initiative in providing input or ideas or suggestions that are useful for developing progress in the Lempe Village office, this is due to the shame factor of young officials who actually have input, suggestions and ideas but didn't dare to say it.